THE EFFECT OF MIDWIVES’ COMMUNICATION ON PREGNANT WOMEN’S SATISFACTION WITH ANTENATAL CARE - Yuliwati Yuliwati (Yayasan Education and Social Center, 2025)
Midwife communication is one of the important factors in antenatal care (ANC) services because it can affect pregnant women's understanding, comfort, and satisfaction with the services received. Effective communication can create a relationship of mutual trust between midwives and pregnant women so as to improve the quality of midwifery services. Pregnant women's satisfaction with ANC services is an important indicator in the success of maternal health services. The purpose of this study aims to analyze the influence of midwifery communication on the satisfaction of pregnant women in antenatal care services based on the results of published research. This research method uses the Systematic Literature Review (SLR) method. The article search was conducted through Google Scholar and PubMed databases with the keywords